Environmental tobacco smoking and its consequences for allergy and asthma in children - a review - Pelczar, Patrycja; Skowron, Aleksandra; Orzeł, Jakub; Przygoda, Aleksandra (Quality in Sport, 2026)
Background. Asthma is one of the most common chronic respiratory diseases in children. Among important non-modifiable environmental risk factors—independent of genetic predisposition—is exposure to environmental tobacco smoke (ETS). Children are particularly vulnerable due to the immaturity of their respiratory and immune systems. Aim. This study reviews the impact of passive smoking on asthma and allergy outcomes in children. Material and methods. Studies were selected from PubMed, including publications from 2020 to 2026. The search terms included “passive smoking,” “asthma,” and “children.” Non-English articles were excluded. Results. The literature shows a strong association between ETS exposure and increased risk of asthma and allergic diseases in children. Both prenatal and postnatal exposure were linked to higher incidence of wheezing, bronchial hyperreactivity, and physician-diagnosed asthma. ETS exposure was also associated with elevated IgE levels and increased sensitization to allergens, as well as a higher prevalence of atopic dermatitis and allergic rhinitis. A dose–response relationship was observed, with greater exposure linked to more severe symptoms. Mechanistically, ETS impairs mucociliary clearance, disrupts epithelial barriers, and promotes airway inflammation. Early-life exposure may have long-term effects on lung development and immune function. Conclusion. ETS is a significant and preventable risk factor for asthma and allergic diseases in children. Reducing prenatal and postnatal exposure is essential to protect respiratory health and improve long-term outcomes.